A virtual bird's eye view: Live streaming nest boxes to continue outreach in the era of COVID‐19. Issue 8 (20th November 2020) - Houtz, Jennifer L.; Mady, Rachael P.; Uehling, Jennifer J.
Abstract: COVID‐19 created a host of challenges for science education; in our case, the pandemic halted our in‐person elementary school outreach project on bird biology. This project was designed as a year‐long program to teach fifth‐grade students in Ithaca, New York, USA, about bird ecology and biodiversity using in‐person presentations, games, activities, and outdoor demonstrations. As a central part of this effort, we set up nest boxes on school property and planned to monitor them with students during bird breeding in the spring. Here, we describe our experiences transitioning this program online: we live streamed nest boxes to the students' virtual classroom and used them as a focal point for virtual lessons on bird breeding and nestling development. In an era of social distancing and isolation, we propose that nest box live streaming and virtual lessons can support communities by providing access to the outdoors and unconventional science learning opportunities for all students. Instituting similar programs at local schools has the potential to increase equitable learning opportunities for students across geographic locations and with varying degrees of physical access to the outdoors and nature. Abstract : COVID‐19 created a host of challenges for science education, including public outreach. Here, we describe our experiences transitioning a fifth‐grade outreach program on bird biology online, and specifically focus on our live streaming of nest boxes as a starting point for virtual lessons on bird breeding and nestling development. We suggest that such virtual programs can promote equitable learning opportunities for students across geographic locations and with varying degrees of physical access to the outdoors and nature, supporting communities through a difficult era of social distancing and isolation.